Retraction Note: Diet restriction inhibits apoptosis and HMGB1 oxidation and promotes inflammatory cell recruitment during acetaminophen hepatotoxicity - Daniel James Antoine; Dominic P. Williams; Anja Kipar; Hugh Laverty; B. Kevin Park (BMC, 2020)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s10020-020-00262-3